Comprehensive insights into host‐pathogen interaction between brown planthopper and a fungal entomopathogen by dual RNA sequencing. Issue 11 (16th July 2021) - Wang, Zheng‐Liang; Pan, Hai‐Bo; Li, Mu‐Yu; Wu, Wei; Yu, Xiao‐Ping
Abstract: BACKGROUND: The brown planthopper (BPH) is one of the most destructive pests of rice, causing tremendous yield and economic losses every year. The fungal entomopathogen Metarhizium anisopliae was previously proved to have great potential for BPH biocontrol. Genome‐wide insight into the insect‐fungus interaction is crucial for genetic improvement of M. anisopliae to enhance its virulence to BPH but still has been poorly explored. RESULTS: Using dual RNA‐seq approach, we present here a global view of host and fungal gene expressions in BPH adults during the fungal infection. The results revealed that BPH could initiate strong defense responses against the fungal attack by upregulating the expressions of a large number of genes, including genes involved in cuticle formation, immune response, cell detoxification and biomacromolecule metabolism. Correspondingly, the fungal entomopathogen could induce a series of genes to infect and modulate BPH, including genes involved in fungal penetration, invasive growth, stress resistance and virulence. Three host defense‐related genes ( NlPCE4, NlPOD1 and NlCYP4DE1 ) were chosen for further function analysis. RNAi‐mediated knockdown of NlPCE4 caused a significant decrease in BPH survival, but no obvious effects on the survival rates were detected by the suppression of NlPOD1 and NlCYP4DE1 . Combination of dsRNA injection and fungal infection could significantly enhance the BPH‐killing speed, as synergistic mortalities were observed in co‐treatments of RNAi and M. anisopliae infection. CONCLUSION: Our study provides a comprehensive insight into molecular mechanisms of host‐pathogen interaction between BPH and M. anisopliae and contributes to future development of new efficient biocontrol strategies for BPH biocontrol. Abstract : Genome‐wide host‐pathogen interaction between brown planthopper and Metarhizium anisopliae was unveiled by dual RNA sequencing. A large number of differentially expressed genes involved in insect defenses and fungal pathogenesis were identified, which could serve as potential targets for genetically modifying the fungus to improve its efficacy against this rice pest. © 2021 Society of Chemical Industry.